Pengembangan Media Pembelajaran Video Animasi Stop Motion Materi Sistem Organ Pencernaan Manusia Siswa Kelas V SDN Palebon 03 Semarang - Dyah Ayu Dwi Astuti; Ferina Agustini; Rofian Rofian (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2021)
The purpose of this research is to develop learning media video animation stop motion the material system organ digestion human feasible and practical for the students of class V SDN Palebon 03 Semarang. This research method using Research and Development with model ADDIE with the technique of analysis of descriptive data. The results of the validation media 2 media experts the first stage of obtaining a value of 75% with the criteria of worth and the second stage to obtain the value of 92% with the criteria very worth it. The results validate the material by 2 experts of the material of the first stage to obtain a percentage of 75% with the criteria of worth and the second stage to obtain the value of 93% with the criteria very worth it. In field trials through the questionnaire responses of teachers to obtain a value of 80% with the criteria very decent and on the questionnaire responses of students to obtain the value of a percentage of 93%. In conclusion media learning video animation stop motion the material system organ digestion human worth and tools used in teaching and learning activities in school.